1994
DOI: 10.1016/0025-5408(94)90045-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering atmosphere on the pore-structure stability of cerium-doped nanostructured alumina

Abstract: Pore-structure stability of pure and Ce-doped alumina in air and argon atmospheres was studied using DTA, TGA, N 2 ads./des, and XRD with a view to understand the importance of the ionic size of the dopant cation on the porestructure stability of alumina. The ionic size effect was studied by heat treating the Ce-alumina system in both oxidizing and reducing atmospheres to have Ce 4÷ (87 pm) and Ce 3÷ (106 pm) respectively. No compound formation between Ce and alumina was observed. In the case of pure alumina t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Barium and rare-earth cations are the most studied dopants, and their behaviors at high temperature are different. [1][2][3][4][5][6][7][8][9][10] Machida et al 4 have reported the excellent stability of barium hexaaluminate (BaO⅐6Al 2 O 3 ) in maintaining a large surface area. They have reported a value of 11 m 2 ⅐g Ϫ1 for powder samples after heating at 1600°C for 6 h, and such a high value has not been reported for any other oxides so far.…”
Section: Introductionmentioning
confidence: 99%
“…Barium and rare-earth cations are the most studied dopants, and their behaviors at high temperature are different. [1][2][3][4][5][6][7][8][9][10] Machida et al 4 have reported the excellent stability of barium hexaaluminate (BaO⅐6Al 2 O 3 ) in maintaining a large surface area. They have reported a value of 11 m 2 ⅐g Ϫ1 for powder samples after heating at 1600°C for 6 h, and such a high value has not been reported for any other oxides so far.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kumar et al [13], this phase can be considered a metastable solid solution based on the monoclinic aluminum oxide stabilized by Ce 4+ ions. The content of the θ-Al 2 O 3 phase is proportional to the content of the α-Al 2 O 3 phase and also depends on the sequence of precipitation of the components.…”
Section: Resultsmentioning
confidence: 99%
“…T HE phase transition from ␥-Al 2 O 3 to ␣-Al 2 O 3 via ␦-Al 2 O 3 and -Al 2 O 3 has been investigated by many workers, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] because this knowledge is very important for creating porous Al 2 O 3 ceramics used as high-temperature catalyst supports, [1][2][3][4][5][6][7][8][9][10][11][12] as well as for the low-temperature sintering and microstructural control of dense Al 2 O 3 ceramics. 13 Because this phase transition is from metastable to stable, the transition temperature is influenced by various factors, such as purity, 1 crystallinity 2 and the agglomerated state 3 of the ␥-Al 2 O 3 cation 4 -9 and anion 10 additives, and heating atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…13 Because this phase transition is from metastable to stable, the transition temperature is influenced by various factors, such as purity, 1 crystallinity 2 and the agglomerated state 3 of the ␥-Al 2 O 3 cation 4 -9 and anion 10 additives, and heating atmosphere. 11 Among these various factors, cation additives can accelerate or retard the transition, depending on the type, 4 -9 amount, 6,7 state, 12 and size 11,14 of the cation. For example, the addition of amorphous SiO 2 has been remarkably effective in retarding phase transition, but crystalline forms of SiO 2 , such as quartz and cristobalite, are reported to accelerate the transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation